Legitimate Interest of Coastal States in Seabed Mining: Indonesia’s Practice - Dhiana Puspitawati; Fransiska Ayulistya Susanto; Moh. Fadli; Mohd Hazmi Mohd Rusli (Faculty of Law, Hasanuddin University, 2024)
Hasanuddin Law Review Volume 9 No.3 Page (299-316)